Analisis Faktor-Faktor Yang Mempengaruhi Minat Migrasi Tenaga Kerja Indonesia (TKI) di Kecamatan Galing Kabupaten Sambas Yang Bekerja di Luar Negeri (Malaysia) - B01110110, Julaiha (Jurnal Curvanomic, 2014)
The title of this research is "Analysis of Factors Affecting Migration Interests Indonesian Workers (TKI) in the district of Sambas district Galing" This study aims to determine the factors that affect the interests of Indonesian Workers who work abroad and to determine changes in the socioeconomic status of workers before and after working in Malaysia. The method of this research is qualitative using data Primer. How to capture primary data using questionnaires, interviews and observations. Furthermore, the data were analyzed by using percentages. The result of this research show that of the five factors that affect the interests of the migration of Indonesian workers (TKI) that working abroad is the most influential foreign wage rate of 39.22 percent, 25.49 percent level of education, number of dependents 21, 57 percent, the type of work at the destination 7.84 percent, 5.88 percent and employment contracts. Â  Keywords: Migration and Indonesian Migrant Workers